Diversity of Ordo Lepidoptera In Mangkok Resort, Sebangau National Park, Central Kalimantan - Achmad Faqih (Hasanuddin University, 2018)
The diversity of the butterfly in Sebangau National Park, particularly in the Mangkok Resort area has different morphological features in each species. The differences distinguish each species between families. Steps to know the diversity species or populations can be measured and identified based on similarities or differences in Shannon-Wiener's diversity analysis. This research was conducted by random purposive sampling using insect net and food trap. Observation and sampling were conducted in the area of natural forest and forest restoration during the dry and rainy seasons. The results showed, the species obtained and identified as many as 25 species from 4 families namely Papilionidae, Nymphalidae, Pieridae and Lycaenidae. Butterflies obtained from food trap are 24 individuals from 5 species. The level of diversity, evenness and richness of the species of butterflies in each region during the rainy and dry seasons which are the location of the study are included in the